If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8m + -8n)(4m + -7n) = 0 Multiply (8m + -8n) * (4m + -7n) (8m * (4m + -7n) + -8n * (4m + -7n)) = 0 ((4m * 8m + -7n * 8m) + -8n * (4m + -7n)) = 0 Reorder the terms: ((-56mn + 32m2) + -8n * (4m + -7n)) = 0 ((-56mn + 32m2) + -8n * (4m + -7n)) = 0 (-56mn + 32m2 + (4m * -8n + -7n * -8n)) = 0 (-56mn + 32m2 + (-32mn + 56n2)) = 0 Reorder the terms: (-56mn + -32mn + 32m2 + 56n2) = 0 Combine like terms: -56mn + -32mn = -88mn (-88mn + 32m2 + 56n2) = 0 Solving -88mn + 32m2 + 56n2 = 0 Solving for variable 'm'. Factor out the Greatest Common Factor (GCF), '8'. 8(-11mn + 4m2 + 7n2) = 0 Factor a trinomial. 8((4m + -7n)(m + -1n)) = 0 Ignore the factor 8.Subproblem 1
Set the factor '(4m + -7n)' equal to zero and attempt to solve: Simplifying 4m + -7n = 0 Solving 4m + -7n = 0 Move all terms containing m to the left, all other terms to the right. Add '7n' to each side of the equation. 4m + -7n + 7n = 0 + 7n Combine like terms: -7n + 7n = 0 4m + 0 = 0 + 7n 4m = 0 + 7n Remove the zero: 4m = 7n Divide each side by '4'. m = 1.75n Simplifying m = 1.75nSubproblem 2
Set the factor '(m + -1n)' equal to zero and attempt to solve: Simplifying m + -1n = 0 Solving m + -1n = 0 Move all terms containing m to the left, all other terms to the right. Add 'n' to each side of the equation. m + -1n + n = 0 + n Combine like terms: -1n + n = 0 m + 0 = 0 + n m = 0 + n Remove the zero: m = n Simplifying m = nSolution
m = {1.75n, n}
| 8x+7x-88=110-7x | | -3x-(-5)+2x=-x-4 | | 1+5x-40=1x-5 | | x+x+4=36 | | -10+x+4-4-5=7x-5 | | 6x+2(7x-4)=92 | | x+2y=29 | | -3x+8=18+4x | | x+2x=62 | | x-3(x-4)+2=14-3(5x+6) | | 3*n-8=2*n+15 | | 4(6x+3x)=12 | | 60k+60k=50k+100 | | x+x+2=62 | | -9+2.5y-.7y+1+6.4y= | | 2.4x=4x-88 | | X^2+5x=46 | | xy-d=mfory | | -18+9x=63 | | 2(x+4)+3(-x)=2(-x) | | -x+1=3x+21 | | 6X-1Y=18 | | 2(4c-1)=8c-2 | | x-2x-3=-x+9 | | 2s+8=22 | | 3(5x-4)-8x=7x-12 | | -7x+14=49-2x | | 10y+8x=314 | | 5y-3=2y-6 | | 4v-12-7v=6-2v | | 2x+5yx+y=3 | | 25=k+23 |